2022
DOI: 10.3390/wevj13070125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Having Solar Panels on the Probability of Owning Battery Electric Vehicle

Abstract: Greenhouse gas emissions, produced by various sectors, including transportation, are significantly impairing the environment and drive climate change. Battery electric vehicles are increasingly seen as a way to alleviate these problems, but they must be charged with electricity produced through environmentally friendly methods. This paper investigates a possible relationship between battery electric vehicles and solar photovoltaic panels using ENABLE.EU household survey data from ten European countries in autu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Urbanization rate (Shafiei et al 2018) was also found to be more important than subsidies, while the KfW study for Germany found strong relations between a high household income and living in houses and in rural regions (KfW 2021). Based on an EU-wide survey analysis, Gezelius and Mortazavi (2022) concluded that there is a significantly positive correlation between having solar panels and purchasing BEVs due to the opportunity for charging at lower costs. Findings of the presented study substantiate these findings, while a moderate value of the determination coefficient (R 2 = 0.452 for the total sample and R 2 = 0.579 for the reduced sample) indicates that a higher difference in electricity price over petrol, combined with a higher share of the population living in suburban houses (that may indicate the opportunity to more easily charge EVs at home), is a strong impetus for buying BEVs.…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization rate (Shafiei et al 2018) was also found to be more important than subsidies, while the KfW study for Germany found strong relations between a high household income and living in houses and in rural regions (KfW 2021). Based on an EU-wide survey analysis, Gezelius and Mortazavi (2022) concluded that there is a significantly positive correlation between having solar panels and purchasing BEVs due to the opportunity for charging at lower costs. Findings of the presented study substantiate these findings, while a moderate value of the determination coefficient (R 2 = 0.452 for the total sample and R 2 = 0.579 for the reduced sample) indicates that a higher difference in electricity price over petrol, combined with a higher share of the population living in suburban houses (that may indicate the opportunity to more easily charge EVs at home), is a strong impetus for buying BEVs.…”
Section: Discussionmentioning
confidence: 99%
“…Using a similar approach, Gezelius and Mortazavi 36 examined household data from ten European countries to analyse a potential connection between PV and EV adoption while controlling for endogeneity between both decisions. Their findings showed a household's likelihood of owning an EV increased by 30% if it also had solar panels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To find this effective wind speed, a thorough computational fluid dynamics (CFD) analysis is carried out to find out (Veffective). ANSYS Fluid is used for the CFD analysis, and the computation is run six times, each time for a different wind speed (5,10,15,20,25,30) mph. The results are shown below.…”
Section: 𝑉 =𝑉 * ( )mentioning
confidence: 99%
“…Finally, a study by Gezelius and Mortazavi [20] revealed a positive correlation between households with solar panels and the likelihood of owning a battery electric vehicle (BEV). This supports the idea that domestic solar charging could boost BEV adoption, contributing to a greener future.…”
Section: Introductionmentioning
confidence: 99%